Research on Corporate Innovation and Compensation Incentives - An Junjie; Masri Bin Abdul Lasi (Asia Pacific Economic and Management Review, 2024)
The optimal contract theory believes that the compensation contract can alleviate the agency contradiction between executives and shareholders. By making the interest goals of executives and shareholders converge, it can enhance the innovation willingness of senior executives to a certain extent, increase the innovation investment of enterprises, and then improve the performance of the company. However, the increase of investment in innovation will not necessarily improve the companys performance, and there may be an endogenous relationship between the two factors, which further complicates the issue of compensation incentive. This article sorts out the relevant literature on enterprise innovation and salary incentive, and discusses the relationship between salary incentive and enterprise innovation and its influence on the endogenous relationship between enterprise innovation and company performance. In addition, the possible influence of executive attachment characteristics on compensation incentive is also discussed.